2015
DOI: 10.1002/ejhf.425
|View full text |Cite|
|
Sign up to set email alerts
|

What does the lay public know about heart failure? Findings from the Heart Failure Awareness Day Initiative

Abstract: Aim & Methods One critical factor enhancing the implementation of successful diagnostic and therapeutic strategies into clinical practice is awareness among the lay public. We describe awareness in a contemporary, multinational convenience sample of subjects attending the Heart Failure Awareness (HFA) Day Initiatives in 2013. Results We analysed 2,438 subjects (Germany 33%, Lithuania 42%, Romania 8%, Slovenia 17%) : 53% were female, 58% were aged >60 years, 11% (had) worked in the medical sector, 82% heard abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 3 publications
3
26
0
2
Order By: Relevance
“…These results were comparable to earlier studies,2, 4 although the percentage of respondents, who knew all three main symptoms of HF, has strongly increased from only 3% reported for the 912 Germans from the population‐based survey study SHAPE conducted in 20022 to 39% in our study. This huge increase in percentage may also partially stem from a selection bias, as people in the present study can be suspected to be interested in health issues and were picked on a health information event at a university.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results were comparable to earlier studies,2, 4 although the percentage of respondents, who knew all three main symptoms of HF, has strongly increased from only 3% reported for the 912 Germans from the population‐based survey study SHAPE conducted in 20022 to 39% in our study. This huge increase in percentage may also partially stem from a selection bias, as people in the present study can be suspected to be interested in health issues and were picked on a health information event at a university.…”
Section: Discussionsupporting
confidence: 92%
“…The SHAPE study reported an overall poor HF awareness in Europeans with one-third of respondents believing that HF was a natural consequence of aging. 2,4 Not having asked the exact same question, still one-third of our population thought that people under 50 years were mostly affected by HF. On the other hand, 57% knew this is actually true for people older than 65, and 67% knew that HF is one of the most common diseases in internal medicine.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The low awareness of previously documented HF, assessed in the context of an interview, in our study sample is in line with the findings of a contemporary, multinational convenience sample of subjects attending the HF Awareness Day Initiatives in 2013 revealing low awareness of HF and its typical signs and symptoms in the lay public as well as important misconceptions regarding the importance and the prognostic implications of HF [45]. The German National Disease Management Guideline “Chronic Heart Failure” [27] as well as the Guideline on HF of the German Society of Primary Care [46] highlight the importance of information about and acceptance of the own disease for therapy adherence.…”
Section: Discussionsupporting
confidence: 85%